TGF-beta1 mRNA upregulation influences chronic renal allograft dysfunction - Pribylova-Hribova, P; Kotsch, K; Lodererova, A; Viklicky, O; Vitko, S; Volk, H-D; Lacha, J (Kidney international, 2006)
Acute rejection (AR) is a dominant risk factor for developing chronic allograft nephropathy (CAN) after kidney transplantation. CAN is characterized by progressive interstitial fibrosis. It has been associated with increased transforming growth factor (TGF)-beta1 expression, however, kinetic studies are absent. We investigated whether intragraft TGF-beta1 expression in various causes of early graft dysfunction may influence late renal allograft dysfunction. A total of 174 human renal biopsies were quantified for TGF-beta1 mRNA expression using real-time reverse transcriptase-polymerase chain reaction. Expression levels were correlated with the Banff histopathological grades, TGF-beta1 immunohistology, and clinical follow-up. TGF-beta1 was most markedly upregulated in AR, CAN, and acute tubular necrosis - delayed graft function compared to non-rejecting controls (P < 0.001). TGF-beta1 expression was heightened in borderline changes (P < 0.01), recurrence of glomerulonephritis, and cyclosporine toxicity (P < 0.05). There was no correlation between intragraft TGF-beta1 expression during AR and short-term outcome of a rejection episode. TGF-beta1 gene overexpression during CAN has been shown to be associated with the increased risk for renal allograft dysfunction 18 months after biopsy (odds ratios 9.9 vs 3.2, respectively). Intragraft TGF-beta1 mRNA expression is significantly upregulated in both AR and CAN. Thus, our results support the hypothesis that TGF-beta1 might play a key role in chronic allograft dysfunction.
Keywords: výsledek terapie; RNA, Messenger; Male; retrospektivní studie; Up-Regulation; ROC Curve; Transforming Growth Factor beta; následné studie; Transplantation, Homologous; Adult; upregulace; dospělí; imunohistochemie; mužské pohlaví; transformující růstový faktor beta1; lidé středního věku; Graft Rejection; Follow-Up Studies; transformující růstový faktor beta; Treatment Outcome; homologní transplantace; Time Factors; Transforming Growth Factor beta1; lidé; ženské pohlaví; Immunohistochemistry; Kidney Transplantation; transplantace ledvin; Humans; časové faktory; rejekce štěpu; Retrospective Studies; Female; ROC křivka; messenger RNA; Middle Aged